PREDICTORS OF LONG-TERM CARE PREFERENCES OF PERSONS WITH MILD COGNITIVE IMPAIRMENT AND DEMENTIA AND CARE PARTNERS. (11th November 2018) - Shepherd-Banigan, M; Jutkowitz, E; Smith, V A; Belanger, E; Plassman, B L; Van Houtven, C; Mor, V
Abstract: A diagnosis of Alzheimer's disease (AD) may catalyze families to consider preferences for long-term care (e.g. informal care, formal home care, nursing home care); clinicians can facilitate these discussions. However, minimal evidence exists about which individual and family-level factors predict preferences and levels of agreement between care recipients and partners. Using CARE IDEAS study data, we examined: R1) which are the most important individual (care recipient and care partner) and family-level predictors of long term care preferences and R2) how frequently care recipients and care partners agree on desired long term care? For R1, we apply a machine learning approach to identify how groups of predictors operate conjointly to influence care preferences. For R2, we examine differences in proportions for paired data and assess the extent of concordance. Our results will inform how clinicians can approach such conversations early in the course of neurodegenerative disease.